Giant anisotropic magnetocaloric effect by coherent orientation of crystallographic texture and rare-earth ion moments in HoNiSi ploycrystal. (July 2020) - Zhang, Hu; Xing, Chengfen; Zhou, He; Zheng, Xinqi; Miao, Xuefei; He, Lunhua; Chen, Jie; Lu, Huaile; Liu, Enke; Han, Wentuo; Zhang, Hongguo; Wang, Yixu; et al.
Abstract: A new concept named "rotating magnetocaloric effect (RMCE)" has been proposed and attracted more attention recently. Unlike the traditional MCE that is achieved by moving the magnetic refrigerant in and out of magnetic field, RMCE can be realized by rotating the anisotropic material within the static field, thus implying the possible higher efficiency and simpler device. However, most studies on RMCE are concentrated on single crystals, which are generally more expensive and difficult to prepare in comparison with polycrystals. Therefore, it is highly desirable to search polycrystalline materials with high RMCE. Here, the textured HoNiSi polycrystal is reported to show a giant RMCE, e.g., the rotating magnetic entropy change (−Δ SR ) are 18.5 and 26.7 J/kg K and rotating adiabatic temperature change (Δ TR ) are 7.0 and 13.4 K under 2 and 5 T, respectively. This giant RMCE over a wide temperature range especially under low field suggests textured HoNiSi as promising material for practical application of rotary magnetic refrigeration. Moreover, the large magnetic anisotropy of HoNiSi is explained by the single-ion magnetic anisotropy theory, and the coherent orientation of crystallographic texture and rare-earth ion moments leads to the large RMCE in the textured HoNiSi polycrystal. This work reveals that the strongly coherent orientation of crystallographic texture and rare-earth ion moments is a key to realize large RMCE in polycrystalline materials. Graphical abstract: Image, graphical abstract